2016
DOI: 10.1007/s00270-016-1491-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Bioabsorbable Self-Expandable Vein Stent-Base Made of Poly(l-lactide) In Vitro and In Vivo

Abstract: PurposeThis study was designed to evaluate performance and tissue response to a self expandable bioabsorbable vein stent base cut from a tube with enhanced stiffness and strength in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Numerous studies in recent years have investigated DES/nanoparticle‐eluting stents coated with biodegradable PLGA and other nanofibres, aiming at sustained drug delivery and a substantially reduced thrombosis . A study also evaluated the performance of a self‐expandable bioabsorbable poly‐ l ‐lactide (PLLA) stent that showed adequate radial force to avoid migration but eventually resulted in a stent failure because the explant demonstrated multiple circumferential fractures . Masuda et al investigated imatinib mesylate, a PGDF receptor tyrosine kinase inhibitor encapsulated bioabsorbable PLGA polymeric nanoparticle‐eluting stent, in a pig coronary artery stent model.…”
Section: Nanoparticle‐des/ges To Negate Isr and Boost Re‐endothelialimentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in recent years have investigated DES/nanoparticle‐eluting stents coated with biodegradable PLGA and other nanofibres, aiming at sustained drug delivery and a substantially reduced thrombosis . A study also evaluated the performance of a self‐expandable bioabsorbable poly‐ l ‐lactide (PLLA) stent that showed adequate radial force to avoid migration but eventually resulted in a stent failure because the explant demonstrated multiple circumferential fractures . Masuda et al investigated imatinib mesylate, a PGDF receptor tyrosine kinase inhibitor encapsulated bioabsorbable PLGA polymeric nanoparticle‐eluting stent, in a pig coronary artery stent model.…”
Section: Nanoparticle‐des/ges To Negate Isr and Boost Re‐endothelialimentioning
confidence: 99%
“…27 A study also evaluated the performance of a selfexpandable bioabsorbable poly-L-lactide (PLLA) stent that showed adequate radial force to avoid migration but eventually resulted in a stent failure because the explant demonstrated multiple circumferential fractures. 28 Masuda et al 29 investigated imatinib mesylate, a PGDF receptor tyrosine kinase inhibitor encapsulated bioabsorbable PLGA polymeric nanoparticle-eluting stent, in a pig coronary artery stent model. The angiographic, histopathological and intravascular ultrasound imaging results of their study showed inhibition of vascular smooth muscle cell (VSMC) proliferation with no adverse effects on endothelial cells in vitro, thereby attenuating in-stent neointimal formation by approximately 50%.…”
Section: Nanoparticle-des/ges To Negate Isr and Boost Re-endotheliamentioning
confidence: 99%